Lactobacillus rhamnosus GG Suppresses Meningitic E. coli K1 Penetration across Human Intestinal Epithelial Cells In Vitro and Protects Neonatal Rats against Experimental Hematogenous Meningitis - Huang, Sheng-He; He, Lina; Zhou, Yanhong; Wu, Chun-Hua; Jong, Ambrose (International Journal of Microbiology, 2009)
The purpose of this study was to examine prophylactic efficacy of probiotics in neonatal sepsis and meningitis caused by E. coli K1. The potential inhibitory effect of Lactobacillus rhamnosus GG (LGG) on meningitic E. coli K1 infection was examined by using (i) in vitro inhibition assays with E44 (a CSF isolate from a newborn baby with E. coli meningitis), and (ii) the neonatal rat model of E. coli sepsis and meningitis. The in vitro studies demonstrated that LGG blocked E44 adhesion, invasion, and transcytosis in a dose-dependent manner. A significant reduction in the levels of pathogen colonization, E. coli bacteremia, and meningitis was observed in the LGG-treated neonatal rats, as assessed by viable cultures, compared to the levels in the control group. In conclusion, probiotic LGG strongly suppresses meningitic E. coli pathogens in vitro and in vivo. The results support the use of probiotic strains such as LGG for prophylaxis of neonatal sepsis and meningitis.